PURIFICATION AND CHARACTERIZATION OF a-GLUCOSIDASE FROM MOSS HYOPHILLA NYMANIANA (FLEISH.) MENZEL - Mishra, Rashmi; Chandra, Ramesh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The present study was undertaken to extract and purify α-glucosidase N-linked glycosylation enzyme from moss Hyophilla nymaniana (Fleish.) Menzel. Methods: Frozen protonemal cells were taken for crude enzyme extraction, and the enzyme α-glucosidase was purified from the prepared crude enzyme extract by ammonium sulfate (NH 4 ) 2 SO 4 precipitation, gel filtration and finally on diethylaminoethyl sephadex column chromatography. Results: The final purification step of the enzyme resulted in 35 fold purification with a recovery of 4%. A single protein band of 72±5 kilodalton was seen on 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The physiochemical characterization of the enzyme reveled the enzyme had a wide pH stability range 4-7 with optimum pH 5 while the temperature stability study revealed the enzyme was stable up to 60°C while the optimum temperature of the purified enzyme was 45°C. The enzyme was strongly inhibited by Hg 2+ and Ag 2+ at 1 mM concentration while Mg ions enhanced the enzyme activity at the same concentration. The kinetic study of the enzyme showed K m and V of the enzyme 5.2 mM/ml and 8.6 U/ml, respectively. Conclusion: The wide pH and temperature stability range show its suitability toward industrial application. max Keywords: α-glucosidase, Hyophilla nymaniana (Fleish.) Menzel. gel filtration, Diethylaminoethyl sephadex column chromatography.